2018
DOI: 10.1007/s10147-018-1245-z
|View full text |Cite
|
Sign up to set email alerts
|

Complications within 90 days after radical cystectomy for bladder cancer: results of a multicenter prospective study in Japan

Abstract: Open radical cystectomy is associated with a high incidence of postoperative complications. Most, however, are of low grade. Our results suggest that obesity, a smoking history, and increasing comorbidity are risk factors for major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 32 publications
2
30
1
1
Order By: Relevance
“…Of note, only two studies partially reported smoking exposure in current smokers [37,44]. Finally, smoking status of patients was not reported in five studies [13,[45][46][47][48]. Surgical approach for RC was open in seven studies, robotic in six studies, and multiple (robotic, laparoscopic, or open) in four studies; finally, surgical approach was not reported/specified in 10 series.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, only two studies partially reported smoking exposure in current smokers [37,44]. Finally, smoking status of patients was not reported in five studies [13,[45][46][47][48]. Surgical approach for RC was open in seven studies, robotic in six studies, and multiple (robotic, laparoscopic, or open) in four studies; finally, surgical approach was not reported/specified in 10 series.…”
Section: Study Populationmentioning
confidence: 99%
“…In these studies, complication rates ranged from 31.7% to 80.5%. This high variability between studies depends mostly on discrepancy in reporting complications (ie, urinary or bowel-anastomotic complications only; overall, medical, and surgical complications), timing of recorded onset of complications (ie, 30 or 90 postoperative days after surgery), urinary diversion (UD) type, and adopted surgical approach (open vs laparoscopic vs robotic) [13,[35][36][37]39,41,[44][45][46][47][48].…”
Section: Overall Postoperative Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among patients after radical cystectomy for treating bladder cancer, general postoperative complications consist of cardiac, cerebral, pulmonary, vascular and gastrointestinal complications, bleeding, seroma, infection, lymphocele, and renal failure. Meanwhile, there is also a high possibility of urinary diversion related intestinal obstruction, anastomotic stenosis or fistula, ureteric obstruction, hydronephrosis, pyelonephritis, and urinary dysfunction [49][50][51]. Thereupon, in view of the incidence of complications and potential mortality, surgeons should choose cystoprostatectomy with full consideration for highly selected LAPC patients and explicitly apprise patients of these risks to obtain their informed consent.…”
Section: Clinical Characterizations and Outcomes Of Cystoprostatectommentioning
confidence: 99%